Factors affecting learner’s satisfaction towards online learning during COVID-19 pandemic: A case study of Vietnam - Thi My Hanh Le; Van Ky Long Nguyen; Tien Son Nguyen; Nhu Hoa Vo (Institute of Advanced Engineering and Science, 2023)
Online learning is being considered a new model of knowledge exchange in modern education. In parallel with the incredible impacts of the global pandemic, this is considered an opportunity to promote the development of online learning globally. Therefore, this study proposed a research framework including four factors affecting learner satisfaction towards online learning during the COVID-19 pandemic at a university, which are system quality, service quality, transformational leadership, and self-efficacy. A questionnaire was conducted online to assess which 131 respondents were representative students from two large private universities in Da Nang: FPT University and Duy Tan University. The results from the regression analysis show that three factors have a positive impact on learner satisfaction during COVID-19. This study concludes that students at private universities in Da Nang prioritize system quality as the most significant factor in their satisfaction with the online learning system, followed by transformational leadership and the last one is self-efficacy. Therefore, it can be more strategic for private organizations, developers, software designers, or even transformation-trained trainers to be emphasized to build a system of processes for implementing online learning for students effectively.